Survey of contemporary practices for disproportionate collapse prevention. (15th November 2019) - Mpidi Bita, Hercend; Huber, Johannes A.J.; Voulpiotis, Konstantinos; Tannert, Thomas
Highlights: This paper presents survey of contemporary practice for disproportionate collapse prevention in buildings. The study presents data on how practitioners around the world apply the existing codes and guidelines. This study compares practices applied to different materials and different regions around the world. The findings also inform on the development for future revisions of building codes for disproportionate collapse prevention. Abstract: This paper summarises contemporary practices and implementations of the existing codes and guidelines with respect to disproportionate collapse prevention. Here, focus is given to structural robustness, defined as the ideal method to decrease the probability of disproportionate collapse in buildings following an initial damage. The results from a global survey with 171 participants (mainly structural engineers) are presented. By comparing practices applied to different structural materials (steel, concrete and timber) and in different regions (Canada, USA, Europe, Australia/New Zealand), areas of improvements for the existing codes and guidelines as well as further research are identified. The results emphasise the importance of including specific recommendations for structural robustness in building codes, applicable to high importance and high occupancy structures. A performance-based approach is preferable, rather than prescriptive requirements, for practical and economic solutions. In addition, the obtained responses highlight the need to further develop the existing indirect and direct methods for disproportionate collapse prevention and structural robustness to include material-specific considerations.